The Impact of Restricting Fixed-Term Contracts on Labor and Skill Demand - Giuseppe Grasso; Konstantinos Tatsiramos (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the impact of increasing the relative cost of fixed-term contracts on labor demand as well as the demand for standard measures of human capital and specific skill requirements. We evaluate a 2018 Italian labor law reform that raised the cost of fixed-term contracts while keeping permanent contract costs unchanged. We employ a difference-indifferences research design, leveraging the variation in firms' exposure to the reform resulting from their diverse reliance on fixed-term contracts due to differing reactions to earlier labor market reforms. Using rich data covering the near universe of online job vacancies in Italy, our findings indicate that the increase in hiring costs for temporary contracts led to a decrease in the relative demand for temporary workers and an increase in the demand for permanent workers. This shift in demand was accompanied by upskilling towards workers with higher levels of human capital and specific skill requirements. When offering jobs under permanent contracts, firms increased their demand for workers with a college degree and social skills. At the same time, they reduced their demand for workers with only a high school degree and no work experience. On the other hand, when offering jobs under fixed-term contracts, firms increased their demand for workers with some work experience and social skills. These findings suggest that while restricting fixed-term contracts encouraged the hiring of permanent workers, such reforms might have unintended consequences by raising the hiring standards for job entry, thereby reducing employment opportunities for less qualified workers.
Keywords: J23; J24; J63; K31; 330; hiring costs; employment protection; dual labor markets; skills